Violation of the vascular platelet hemostasis as a risk factor of primary open-angle glaucoma progression - N. I. Kurysheva; V. N. Trubilin; E. Yu. Irtegova; A. N. Yasamanova (Oftalʹmologiâ, 2015)
Purpose: to study the vascular platelet hemostasis parameters in primary open-angle glaucoma (POAG).Patients and methods: ophthalmic examination, plasma level of spontaneous and induced platelet aggregation and von Willebrand factor (vWF) were performed in 67 patients with high pressure glaucoma (HPG), 41 patients had normal tension glaucoma (NTG) and 38 were in control group. Period of study was 36 months. The statistical analysis included standard methods of variation statistics. The threshold P value for statistical significance was 0.05.Results: platelet aggregation was increased in glaucoma (adrenalin-induced aggregation in HPG was 63,34 %±20,42 %, р = 0,043, in NTG 62,35 %±11,53 %, р = 0,047, in comparison with control group — 49,71 %±15,96 %; ristocetin-induced aggregation in HPG was 79,45 %±28,63 %, р = 0,015, in NTG 68,98 %±12,42 %, р = 0,022, and in control group 53,56 %±8,80 % accordingly); the mean level of vWF was increased in HPG (113,25 %±24,31 %, р = 0,009) and NTG (106,85 %±21,02 %, р = 0,012) in comparisonwith control group (93,86 %±17,13 %). Patients with normal level of vWF did not have a progression of glaucoma optical neuropathy. Patients with normalized level of vWF under treatment had significant improvement of MD in 6 months (from –4,916±5,121 to –4,103±4,658, р = 0,037) and were stable in the further follow up period. Patients with increased level of vWF had deterioration of MD in 36 months (from –4,616dB±8,426 dB to –5,974dB±8,852 dB, р = 0,042), increase of cup / disk ratio (from 0,59±0,21 to 0,66±0,24, р = 0,041) and thinning of average RNFL according to HRT and OCT (from 0,21±0,09 μm to 0,17±0,08 μm, р = 0,04; from 74,37±15,34 μm to 69,44±15,12 μm, р = 0,04).Conclusion. The obtained results indicate the importance of the vascular platelet hemostasis in POAG pathogenesis and the perspectives of its correction in glaucoma treatment.